Bauhinia s.s. (Fabaceae−Cercidoideae) from Baixada Cuiabana, Mato Grosso, Brazil: a neglected center of diversity for the genus - Amorim, Daniele Dos Santos De; Pessoa, Edlley (Phytotaxa, 2025)
Baixada Cuiabana (Cuiabá lowlands) is a region in the south-central part of the state of Mato Grosso, comprehending the Pantanal and Cerrado phytogeographical domains. The flora of the region is scarcely known, but high levels of plant diversity are expected. Therefore, the goal of the present study is to contribute to the taxonomy of genus Bauhinia in Baixada Cuiabana, presenting a taxonomic synopsis with descriptions, identification keys, typifications, photographs, geographical distribution data and taxonomic commentary. We confirm the occurrence of 16 species of Bauhinia in the study area, corresponding to 73% of the species of the genus registered in the state of Mato Grosso, and ca. 25% of the Brazilian species. Given the reduced geographical area, the region can be considered a neglected center of diversity of the genus. Among the recorded species, five are endemic to Brazil, two of which are restricted to Baixada Cuiabana: B. caloneura Malme and B. malmeana Vaz & Lewis. Besides, five lectotypifications are presented for B. bauhinioides, B. holophylla, B. longifolia, B. marginata, and B. pentandra, three second-step lectotypifications for B. caloneura, B. cupulata and B. pulchella, and one neotypification for B. brevipes.